Pengembangan media e-modul berbantuan Canva dengan model Problem Based Learning (PBL) untuk meningkatkan kemampuan berpikir kritis siswa Sekolah Dasar - Ai Sutiani; Wikanengsih; D. Fadly Pratama (IKIP Siliwangi, 2026)
This research is motivated by the low critical thinking skills of third-grade elementary school students in Science subjects, caused by limited interactive teaching materials and passive learning models. This study aims to develop, test the feasibility of, and analyze the effectiveness of a Canva-assisted e-modul using the Problem-Based Learning (PBL) model in improving students' critical thinking skills. The research employs the Research and Development (R&D) approach using the Borg and Gall model, adapted into 10 developmental stages. Expert validation results indicate that the e-modul is classified as